Soil microbial populations of several land use types in Makbon District, Sorong Regency, Indonesia - Febrianti Rosalina; Muzna Ardin Abdul Gafur; Zulkarnain Sangadji; Riskawati Riskawati (Caspian Journal of Environmental Sciences)
Degradation of soil function can damage the surrounding ecosystem. Soil fertility is important to plant growth because it is the source of nutrition. One of the factors determining soil fertility is the soil's biological aspects. The study aims to identify the soil microorganism population in the area with the potential for agriculture in Makbon District. The research steps included sampling, media preparation, preparation of dilution series, isolation, and soil microorganism calculation. Based on the land usage, samples K1, M1, and M3 were mapped as primary forests; K2 was a banana farm; B1, K3, M2, and T1 were mixed farms; while T2 and T3 were for horticulture. The findings show that based on the calculation of the total bacteria using the TPC model, the biggest population was found in the mixed farms among various land usages. T2 exhibited  the biggest number of bacteria (1,2 × 105 CFU mL-1) compared to other samples, followed by T1 with the total bacteria of 1.1 × 105 CFU mL-1 and M2 with the total bacteria of 1.0 × 105 CFU mL-1. On the other hand, sample K3 displayed the biggest number of fungi colonies, 1.0 × 103 CFU mL-1. The biggest number of phosphate-solubilizing bacteria colonies were found in Sample B1, which was 1.8 × 105 CFU mL-1. Furthermore, the biggest number of Nitrobacter colonies was found in sample M3, which was 1.2 × 104 CFU mL-1. The study is expected to provide a description and information about the ground microbe population in agroforestry and mixed farms to be considered in the next studies.